Exploration of Cultural Values Chinese In Context Evangelism at GKPJ Kuala Tungkal, Jambi: A Study Case Based Matthew 28:19-20 - Rinawati Rinawati; Stasha Diva Sudijanto; Oktapianus Parintak; Suranto Suranto (LPPM Universitas PGRI Sumatera Barat, 2025)
This aim For explore values culture Influential Chinese to implementation evangelism at the Jambi Protestant Christian Church (GKPJ) Kuala Tungkal. Through approach qualitative with method studies cases and questionnaires open against 10 respondents, research This identify values main like family, respect to ancestors, politeness, harmony, and collectivity. Research results show that values culture the can become an effective contextual media in evangelism, during integrated with understanding Theologically sound. The main challenge lies in the practice of ancestor veneration, which has the potential to create tension with Christian faith. The study's conclusions emphasize the importance of a contextual and culturally based evangelism approach, in accordance with the Great Commission in Matthew 28:19-20.